Port infrastructure finance - Meersman, Hilde; Voorde, Eddy Van de; Vanelslander, Thierry (Informa Law from Routledge, 2014)
This book provides an expert analysis of alternative investments routes and the investment strategies available to the major port players, and is a much-needed guide to expanding the investor base for private debt funding of projects from loan providers to bond investors.